Toward a Molecular Classification of Colorectal Cancer: The Role of MGMT - Minoo, Parham; Minoo, Parham; Minoo, Parham (Frontiers in Oncology, 2013)
O6-methylguanine DNA methyltransferase (MGMT) is a DNA repair enzyme with the ability to protect cells from DNA mutations by removing alkyl groups from the O6 position of guanine. Colon mucosa is exposed to the direct effects of environmental carcinogens and therefore maintaining a proficient DNA repair system is very important to stay protected against DNA mutagenesis. Loss of MGMT expression is almost exclusively associated with methylation of CpG islands in the MGMT gene promoter region which is found in approximately 40% of colorectal cancers. The role of MGMT loss in colorectal tumorigenesis is complex but numerous studies have documented methylation of this gene even in the normal appearing mucosa as well as in aberrant crypt foci, suggesting that MGMT methylation can be regarded as an early event or “field defect” in colon cancer neoplasia. The focus of this perspective is the role of MGMT in different pathways of colorectal carcinogenesis as well as the implication of this molecule in treatment decisions in colorectal cancer patients.